(untitled) (Scientific journal of the Fergana State University, 2026)
This article discusses the role of the irrigation system in the republic’s agriculture. The policy of the Soviet government to increase cotton yields and the reforms implemented in the irrigation system as a result are presented. Although the construction of water structures for the development of new lands, the digging of new canals and ditches were carried out for the purpose of obtaining crops, they were carried out with the labor of the local population. In addition, the emergence of the Aral Sea problem during this period had a very negative impact not only on the irrigation system, but also on the ecology.